Distribution of palpigrades (Arachnida, Palpigradi) in Slovenia with a new record of Eukoenenia austriaca (Hansen, 1926) - Maja Zagmajster; Ľubomir Kováč (Natura Sloveniae)
So far, three species of the palpigrade genus Eukoenenia have been found in Slovenia, predominantly in caves in the southern parts of the country: Eukoenenia austriaca (Hansen, 1926), E. spelaea (Peyerimhoff, 1902) and E. gasparoi Condé, 1988. Distributional map of the species mentioned is provided. In 2005, a subadult male of E. austriaca was collected in Migutovo brezno Cave, which is the first palpigrade record from the northwestern part of Slovenia. It was found on the surface of a small puddle in clay sediment deposited on the rocks of a narrow channel about 100 m from the cave entrance and about 15 m below the surface. Based on opisthosomal chaetotaxy, it differs from the nominal subspecies, and additional specimens from the locality would be required for exact subspecific determination. Microhabitats inhabited by palpigrades and collecting methods used are discussed.